MENGENAL LEBIH DEKAT EKONOMI SYARIAH - Latifah, Eny; Abdullah, Rudi (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM Azramedia indonesia, 2023)
Post-pandemic is a period of reform and improvement in various economic sectors in order to create a stable and strategic economy. The significant impact is felt by MSME players in terms of sales. The purpose of this community service is to provide training to MSME players (the main target of PKK) in Bulangan Village, Gresik Regency. The service method used is Participatory Action Research (PAR) which is to provide learning in overcoming a problem. The results of the service are the socialization of digital marketing by introducing e-comerce and how to create it. Providing training on the CANVA application platform in designing MSME product logos. The achievement obtained by MSMEs or PKK is that they already have an e-commerce account and are ready to buy and sell digitally